(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This in the article pharmaceuticals in enterprises accounting account system improvement issues financial of the report international based on IFRS seeing issued pharmaceutical industry to oneself typical features, product of the cycle complexity and working release stages abundance this to the field adapted account requires policy. Therefore, in the article international to standards appropriate account of conduct advantages, its financial transparency, investment to attractiveness and enterprise to the efficiency impact analysis made.